Kajian sifat listrik bayam merah dan daun kelor sebagai fotosensitizer pada DSSC solar cell - Nurlaila Rajabiah; Tri Cahyo Wahyudi (TURBO [Tulisan Riset Berbasis Online], 2022)
DSSC (Dye Sensitized Solar Cell) uses dye as a sensitizer material which is used as an electron donor to TiO2 nanoparticles and uses an electrolyte as an electron transport medium. One of the dye extracts of purple spinach and moringa leaves used as a photosensitizer is chlorophyll extract or anthocyanin. The nature of chlorophyll which is able to absorb light is a function of the dye in DSSC. Making Moringa leaf and red spinach leaf dye after being blended, dried and ground into powder. Then the Moringa leaf powder was mixed with 70% ethanol with the ratio of Moringa leaves and ethanol, namely 1:2, 1:3, and 1:4. Meanwhile, red spinach leaf powder was mixed with ethanol solution in a ratio of 1:3. DSSC fabrication shows that the voltage, current, and power produced increases with the increasing amount of ethanol used, namely 1.879 mW, 1.573 mW, and 1.98 mW. Meanwhile, red spinach leaves mixed with ethanol in a ratio of 1:3 showed that the results were higher than Moringa leaves. So from the results of DSSC Solar Cell fabrication using Moringa leaves and red spinach leaves, it shows that there is light absorption from these materials and an increase in the conductive properties of Moringa and red spinach DSSCs.